Can I let you go, my love?: the emotional and spiritual journey of a woman following the loss of her husband - Dijk, Kay van (The Lutterworth Press, 2010)
Combining the poignant appeal of a love story cut short with the theme of personal growth and the spiritual search for meaning, this book will help to give comfort to those who have shared the pain of bereavement. It shows them that they are not alone, and that the cycle of grieving is normal and that life does get better. Presented as a verse journal, Can I Let You Go, My Love? is more than an outpouring of one womanis experience of bereavement and life beyond grief. It is also a way of letting other people know what the bereaved are going through and so broadening understanding. The verses are full of lifeis lessons and the thoughts and feelings expressed are powerful, profound and heart-rending. It is a book that not only can be used bycounsellors and their clients (the manuscript has already been adopted as a therapeutic aid by counsellors) but is just the gift to give to a friend who has lost a loved one or who is going through a crisis in life. Can I Let You Go, My Love? was cited as an Outstanding Contender for the CRUSE Excellence in Communication Award 1997.